Poor dental hygiene and periodontal health in nursing home residents with dementia: an observational study - Zenthöfer, Andreas; Baumgart, Dominik; Cabrera, Tomas; Rammelsberg, Peter; Schröder, Johannes; Corcodel, Nicoleta; Hassel, Alexander J. (Odontology, 2017)
Poor oral health conditions are well documented in the institutionalized elderly, but the literature is lacking research on relationships between dementia and periodontal health in nursing home residents. The purpose of this cohort study, therefore, was to assess whether dementia is associated with poor oral health/denture hygiene and an increased risk of periodontal disease in the institutionalized elderly. A total of 219 participants were assessed using the Mini Mental State Examination (MMSE) to determine cognitive state. According to the MMSE outcome, participants scoring ≤20 were assigned to dementia group (D) and those scoring >20 to the non-dementia group (ND), respectively. For each of the groups D and ND, Gingival Bleeding Index (GBI) and Denture Hygiene Index (DHI) linear regression models were used with the confounders age, gender, dementia, number of comorbidities and number of permanent medications. To assess the risk factors for severe periodontitis as measured by the Community Index of Periodontal Treatment Needs, a logistic regression analysis was performed. Statistical analysis revealed no significant differences of GBI as well of DHI for demented and healthy subjects (p > 0.05). Severe periodontitis was detected in 66 % of participants with dementia. The logistic regression showed a 2.9 times increased risk among demented participants (p = 0.006). Oral hygiene, denture hygiene and periodontal health are poor in nursing home residents. The severity of oral problems, primarily periodontitis, seems to be enhanced in subjects suffering from dementia. Longitudinal observations are needed to clarify the cause-reaction relationship.